Mood Disorders and Severity of Addiction in Alcohol-Dependent Patients Could Be Mediated by Sex Differences - Palma-Álvarez, Raul F.; Rodríguez-Cintas, Laia; Abad, Alfonso C.; Sorribes, Marta; Ros-Cucurull, Elena; Robles-Martínez, María; Grau-López, Lara; Aguilar, Lourdes; Roncero, Carlos (Frontiers in Psychiatry, 2019)
Background: Alcohol dependence is highly prevalent in the general population, some differences in alcohol use and dependence between women and men have been described, including outcomes and ranging from biological to social variables. This study aims to compare the severity of alcohol dependence with clinical and psychopathological characteristics between sexes. Methods: A cross-sectional descriptive study was conducted in alcohol-dependent outpatients, the recruitment period was seven years. The assessment of these patients was carried out by obtaining sociodemographic characteristics and using the SCID-I, SCID-II, EuropASI, BDI and STAI scales. Variables were compared and analyzed. Results: The sample was composed by 178 patients (74.2% males and 25.8 females) with a mean age of 46.52±9.86. No sociodemographic differences were found between men and women. Females had higher rate of suicide attempts and depression symptoms at the treatment onset. When results of EuropASI were compared, females had worse psychological and employment results than males. According to consumption variables, males had an earlier onset of alcohol use, more regular alcohol use, and develop alcohol dependence earlier than females. Conclusions: According to results, there are sex-dependent differences (severity and other variables such as mood or suicide) in alcohol dependence. Thus, this may implicate the need of future specific research and treatment programs based on the specific necessities of each sex.